Effectiveness of acupuncture for headache in post-stroke patients - Kovalenko, Olga; Chizhykova, Maryna (Psychosomatic Medicine and General Practice, 2018)
Introduction. Vascular and cerebrovascular diseases remain an actual problem of modern society. More than 70% of post-stroke patients suffered from different pains. Although a headache is the common complaint of post-stroke patients it is not described good in specialized literature and its pathophysiology has not yet been sufficiently studied. In order to relieve headaches, the patients usually use a lot of medicaments often without an agreement with a doctor. Since unnecessary polypharmacy is ineffective and leads to a wide range of adverse effects, the search for pathogenically valid and effective alternative approaches deserves the great attention. Acupuncture is one of such approaches. Methods. We analyzed 2 groups of patients who had the stroke in anamnesis and suffered from a headache: the main (acupuncture) group (n = 30) that underwent acupuncture and traditional medications and the control group that received medication alone (n = 30). The average age of patients in the main group was 70 (SD 8.06) years. Among them 13 women and 17 men. The average age of participants in the control group was 70.3 (SD 9.00) years and it included 8 and 22 individuals of male and female gender. In both groups, the ischemic stroke type predominated. Most patients in both groups were in residual stroke period. Along with the corporal acupuncture we used a combined method which included an effect on several microsystems. Evaluation of a headache was based on 4 criteria: intensity, duration, characteristics, and localization. Results. The data analysis showed that the complex treatment of a headache including combined acupuncture method statistically significantly (p<0.05) affects three indicators of a headache - intensity, duration, and characteristics. The pain localization had a tendency to positive changes (p<0.1). Control group showed good results (p<0.05) only on two headache indicators - intensity and duration, whereas the effect of treatment on pain characteristics and localization was not significant. The comparative analysis of the treatment results of the two groups demonstrated the statistically significant positive effect (p<0,05) in favor to acupuncture on the four headache criteria: intensity, duration, characteristics, and localization. Conclusion. Acupuncture in the complex treatment of post-stroke patients significantly reduces a headache in comparison to standard treatment alone. It can allow improving the effectiveness of rehabilitation and quality of life.